Analisis Efektivitas Touchpoint online dan Offline terhadap Keputusan Pembelian Rumah Subsidi di Tasikmalaya - Rangga Purnama; Adi M. Nur Ihsan; Isyana Rahayu (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the effect of online and offline touchpoints in the customer journey on the purchase decision of subsidized housing units at PT Prima Anugrah Utama in Tasikmalaya. This study employed a quantitative approach using a survey method involving 75 consumers who had completed a housing purchase or mortgage agreement. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results show that the online touchpoint has no significant effect on purchase decisions (t = -0.131; p = 0.896). In contrast, the offline touchpoint has a positive and significant effect on purchase decisions (t = 13.975; p = 0.000). The model explains 83.3% of the variation in purchase decisions. These findings indicate that online touchpoints primarily provide initial information, while offline interactions play a more important role in finalizing purchase decisions. Future research should consider financing accessibility and credit eligibility.